A Pulsed‐Dose Study Evaluating Chronic Toxicity of Chlorothalonil to Fish: A Case Study for Environmental Risk Assessment. (19th June 2019) - Hamer, Mick; Maynard, Samuel K.; Schneider, Suzanne
Abstract: Chlorothalonil is a fungicide which is highly toxic to aquatic organisms. However, in natural aquatic environments, it is very rapidly degraded, with a half‐life typically in hours, reducing exposure of aquatic organisms and the potential for effects. In standard regulatory studies looking at the chronic toxicity of chlorothalonil to fathead minnow, the most sensitive endpoint was fecundity. A standard fish full–life cycle study, where chlorothalonil concentrations were maintained constant throughout, resulted in a no‐observed‐effect concentration (NOEC) of 1.4 µg/L. Comparing peak modeled exposure concentrations to this NOEC can result in the chronic risk to fish being considered unacceptable. The present study investigated the effect on fecundity in fathead minnow using a fish short‐term reproduction assay. Five different exposure profiles were employed with time‐varying concentrations based on realistic worst‐case modeled environmental exposure profiles, multiplied by an assessment factor of 10, which resulted in maximum measured concentrations up to 15.5 µg/L. There were no effects on fecundity from any of the exposure profiles tested. Therefore, based on these more realistic exposure profiles, the chronic risk to fish could be considered acceptable if these exposures were deemed to be representative of the worst case. Environ Toxicol Chem 2019;38:1549–1559. © 2019 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.